THE EFFECT OF WAIST CIRCUMFERENCES MORE THAN NORMAL ON THE INCIDENT OF CORONARY HEART DISEASE - Pria Wahyu; Ratna Hidayati (Universitas Airlangga, 2017)
Introduction: Coronary heart disease is known as the most common disease that causes mortality in the world, one of the examination to identify the risks of coronary heart disease is measuring waist circumference. The purpose of this study was to identify correlation between large waist circumferences and the incident of coroner heart disease. Method: Design used in this study was analytic observational (retrospective) with cross sectional approach. There were 63 respondents which sampling by simple random sampling. The independent variable was waist circumferences and the dependent variable was coronary heart disease. Data were collected by direct observation then analyzed by spearman correlation statistic test with significance level α≤0.05. Result: The result showed that waist circumferences more than normal had significant correlation with the incident of coronary heart disease (p=0.02). Analysis: It can be concluded that there was correlation between waist circumferences more than normal and the incident of coronary heart disease to the clients with coroner cardiac disease. Discussion: Earlier screening and detection is needed to prevent coronary heart disease.